Effects of Pelvic Rocking and Deep Breathing Relaxation Exercises on the Progression of the Active Phase of the First Stage of Labor - Gusrida Umairo; Lutfi Nurjanah; Indriyani Suntara; Jati Prasetianingsih; Liesiana Puspasari (Jurnal Penelitian Pendidikan IPA, 2024)
Prolonged labor or undeveloped labor is one of the complications in childbirth. Where prolonged labor is labor that lasts more than 24 hours in primi and more than 18 hours in multi. The purpose of this research is for the Influence of Pelvic Rocking Exercise and Slow Deep Breathing Relaxation on the Progress of the First Stage of Labor among mothers giving birth in Indonesia in 2024. Research methods This is a pre experimental quantitative research with a group compilation statistical design. The data analysis used is univariate and bivariate analysis using the Mann Whitney hypothesis test, which is a non-parametric test that measures differences equivalent to the independent T test in parametric measurements. The p-value result was 0.000. This shows that there is a significant influence of pelvic rocking exercise and slow deep breathing relaxation on the progress of the first stage of labor in 2024. This pelvic rocking exercise and slow deep breathing relaxation intervention can be applied by the birthing mother so that the mother can give birth safely, comfortably and in a quicker time than without intervention.